Achieving long-life Prussian blue analogue cathode for Na-ion batteries via triple-cation lattice substitution and coordinated water capture. (July 2019) - Xie, Bingxing; Zuo, Pengjian; Wang, Liguang; Wang, Jiajun; Huo, Hua; He, Mengxue; Shu, Jie; Li, Haifeng; Lou, Shuaifeng; Yin, Geping
Abstract: Prussian blue and its analogues have attracted tremendous interests as cathode materials for sodium ion batteries because of their low cost and high capacity. However, their commercial applications are hindered by low capacity utilization and insufficient cycle life. Here, we report on a MnCoNi-co-doped Prussian blue analogue with high purity and crystallinity by a citrate-assisted controlled crystallization process. Moreover, a novel strategy of in situ capturing for residual coordinated water during sodiation/desodiation process is proposed to achieve a high cyclability by using the aluminium chloride Lewis acid as electrolyte additive. The reversible cubic-rhombohedral phase transition is revealed by in situ X-ray diffraction, ex situ X-ray absorption spectroscopy and transient electrochemical impedance spectroscopy. The MnCoNi-co-doped composite delivers a capacity of 111 mAh g −1 even at 1C and retains a capacity retention of 78.7% after 1500 cycles for sodium ion batteries. This work provides important insights on eliminating the parasitical coordinated water in lattice and modulating the crystallinity to develop high-performance Prussian blue and its analogues. Graphical abstract: Image 1 Highlights: MnCoNi-co-doped PBA is synthesized by a citrate-assisted controlled crystallization process. The structure evolution of PBA is revealed by in-situ XRD, ex-situ XAS and transient EIS. The co-substitution strategy realizes the regulation of the lattice and stress. AlCl3 electrolyte additive can capture the coordinated H2 O during cycling.